Comparing Cost-effectiveness of X-Stop With Minimally Invasive Decompression in Lumbar Spinal Stenosis: A Randomized Controlled Trial. Issue 8 (15th April 2015) - Lønne, Greger; Johnsen, Lars Gunnar; Aas, Eline; Lydersen, Stian; Andresen, Hege; Rønning, Roar; Nygaard, Øystein P.
Abstract : Study Design: Randomized clinical trial with 2-year follow-up. Objective: To compare the cost-effectiveness of X-stop to minimally invasive decompression in patients with symptomatic lumbar spinal stenosis. Summary of Background Data: Lumbar spinal stenosis is the most common indication for operative treatment in elderly. Although surgery is more costly than nonoperative treatment, health outcomes for more than 2 years were shown to be significantly better. Surgical treatment with minimally invasive decompression is widely used. X-stop is introduced as another minimally invasive technique showing good results compared with nonoperative treatment. Methods: We enrolled 96 patients aged 50 to 85 years, with symptoms of neurogenic intermittent claudication within 250-m walking distance and 1- or 2-level lumbar spinal stenosis, randomized to either minimally invasive decompression or X-stop. Quality-adjusted life-years were based on EuroQol EQ-5D. The hospital unit costs were estimated by means of the top-down approach. Each cost unit was converted into a monetary value by dividing the overall cost by the amount of cost units produced. The analysis of costs and health outcomes is presented by the incremental cost-effectiveness ratio. Results: The study was terminated after a midway interim analysis because of significantly higher reoperation rate in the X-stop group (33%). The incremental cost for X-stop compared with minimally invasive decompression was [Euro sign]2832 (95% confidence interval: 1886–3778), whereas the incremental health gain was 0.11 quality-adjusted life-year (95% confidence interval: −0.01 to 0.23). Based on the incremental cost and effect, the incremental cost-effectiveness ratio was [Euro sign]25, 700. Conclusion: The majority of the bootstrap samples displayed in the northeast corner of the cost-effectiveness plane, giving a 50% likelihood that X-stop is cost-effective at the extra cost of [Euro sign]25, 700 (incremental cost-effectiveness ratio) for a quality-adjusted life-year. The significantly higher cost of X-stop is mainly due to implant cost and the significantly higher reoperation rate. Level of Evidence: 2 Abstract : This randomized controlled trial compares cost-effectiveness of X-stop to minimally invasive decompression. The study was terminated after a midway interim analysis because of a significantly higher reoperation rate. Exhibiting a nonsignificant better effect, it is a 50% likelihood that X-stop is cost-effective at the extra cost of [Euro sign]25, 700 for a quality-adjusted life-year.